2015
DOI: 10.1016/j.molimm.2014.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a common mucosal immune system in the pig

Abstract: The majority of lymphocytes activated at mucosal sites receive instructions to home back to the local mucosa, but a portion also seed distal mucosa sites. By seeding distal sites with antigen-specific effector or memory lymphocytes, the foundation is laid for the animal's mucosal immune system to respond with a secondary response should to this antigen be encountered at this site in the future. The common mucosal immune system has been studied quite extensively in rodent models but less so in large animal mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 113 publications
(134 reference statements)
0
23
0
Order By: Relevance
“…Mucosal vaccines have some advantages compared with traditionally vaccines, and most infections occur at a mucosal surface or spread from mucosal surfaces [201]. Studies have shown that mucosal administration could provide an early defense against invading pathogens, as the local antibodies of the mucosa work faster than serum antibodies, are higher in level, and have a greater maintenance time [202,203]. The process of immunity is shown in Figure 6 [204].…”
Section: Applications Of Chitosan Derivative Nanoparticles In Mucosalmentioning
confidence: 99%
“…Mucosal vaccines have some advantages compared with traditionally vaccines, and most infections occur at a mucosal surface or spread from mucosal surfaces [201]. Studies have shown that mucosal administration could provide an early defense against invading pathogens, as the local antibodies of the mucosa work faster than serum antibodies, are higher in level, and have a greater maintenance time [202,203]. The process of immunity is shown in Figure 6 [204].…”
Section: Applications Of Chitosan Derivative Nanoparticles In Mucosalmentioning
confidence: 99%
“…Moreover, the concept of a ''common mucosal immune system'' supports the idea that B and T cells primed locally in an initial mucosal site can seed distantly to other mucosal or lymphoid tissues. By seeding distal sites with antigen-specific effector or memory phenotypes, this mucosa-derived immunity would protect the host against any pathogen encountered in the future, irrespective of the portal of entry (Wilson and Obradovic, 2015), thus establishing ''functional connectiveness'' within the immune system (Kiyono and Fukuyama, 2004;Kunisawa et al, 2008;McGhee et al, 1992). This notion could explain the potential efficacy of immune checkpoint blockers such as anti-PD1/PD-L1 Ab against lung cancers in the context of intestinal Bifidobacteriumdependent T cell function resetting (Sivan et al, 2015).…”
Section: Conceptualizing Putative Mechanistic Links Between Gut Micromentioning
confidence: 99%
“…No data was found on immune function in minipig (information on immune function development in the pig is given by [79][80][81]). The data in rat and mouse could not be compared with the human data, because the immune parameters were very different.…”
Section: Interspecies Differences In Hematopoiesis Lymphoid Organ Anmentioning
confidence: 99%